Filosofi Mutu dan Mutu Pendidikan - Yayuk Zulaikah; Akhyak Akhyak; Asy’aril Muhajir; Nur Effendi; Liatul Rohmah (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
The purpose of writing this article is to understand the philosophy of quality and quality of education. Library research is research carried out by reviewing various journals and related reference books. The results of his research show that Quality is a philosophy and methodology that helps institutions to plan changes and set agendas in the face of excessive external pressures. the philosophy of quality has changed and no longer refers to the classical view. This change can be seen from the quality orientation which refers to consumer needs and criteria. The quality philosophy generally adopted today is that product quality is not only determined by the producer but is determined by the consumer (customer). Education quality is the ability of educational institutions and systems to empower educational resources to improve quality in accordance with educational expectations or goals through an effective educational process. The scope of educational quality cannot be separated from three models, namely: input, process and output. In efforts to improve quality using this model, there are several criteria and characteristics that must be met in each scope. Above the national education standards, there are eight (8) things that must be considered to create quality education, namely Content Standards, Process Standards, Educator and Education Personnel Standards, Facilities and Infrastructure Standards, Management Standards, Financing Standards and Educational Assessment Standards.